2015
DOI: 10.1016/j.eml.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Pyro-paraelectricity

Abstract: The electrical responses of materials and devices subjected to thermal inputs, such as the Seebeck effect and pyroelectricity, are of great interest in thermal-electric energy conversion devices. Of particular interest are phenomena which exploit heterogeneities in the mechanics of heterostructured materials and systems for novel and unexplored thermal-electric responses. Here we introduce a new mechanism for converting thermal stimuli into electricity via structural heterogeneities, which we term "pyro-parael… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Since the gradient scales inversely with the size of the specimen, typically, strain gradients within nanostructures are much greater than their macroscopic counterparts. Experiments have convincingly illustrated the significance of flexoelectricity at the nanoscale and demonstrated its potential to open up novel and unique functionality that cannot be achieved through other means [20][21][22][23][24][25]. Concurrent theoretical studies have greatly advanced our understanding of the microscopic origins of flexoelectricity.…”
Section: Introductionmentioning
confidence: 97%
“…Since the gradient scales inversely with the size of the specimen, typically, strain gradients within nanostructures are much greater than their macroscopic counterparts. Experiments have convincingly illustrated the significance of flexoelectricity at the nanoscale and demonstrated its potential to open up novel and unique functionality that cannot be achieved through other means [20][21][22][23][24][25]. Concurrent theoretical studies have greatly advanced our understanding of the microscopic origins of flexoelectricity.…”
Section: Introductionmentioning
confidence: 97%
“…With the increasing demand for clean energy and reliable energy sources for self-powered or portable systems, the exploration of energy harvesting materials, which convert different forms of ambient energy sources into electrical energy, is currently a topic of intense interest. Thermal energy is a ubiquitous and abundant energy source, and various physical effects of materials have been exploited to convert thermal energy into electrical energy. Thermoelectric materials convert the temperature gradient of materials into electrical energy using the well-known Seebeck effect. , Materials possessing spontaneous polarization can convert a change in their temperature into electrical power because of the temperature dependence of spontaneous polarization (the so-called pyroelectric effect). , Nonpolar materials normally do not have a pyroelectric effect, but recent studies revealed that by exploiting flexoelectricity, an electromechanical effect whereby the electric polarization is generated by a strain gradient, a pyroelectric-like response could be generated by the temperature dependence of the flexoelectric polarization in inhomogeneously strained thin film. Because the flexoelectric effect is normally weak, the pyroelectric-like response from the flexoelectric effect is typically much lower than that from the pyroelectric effect of polar materials . To convert the thermal energy into electricity by these physical effects, special temperature conditions (i.e., a space variation of the temperature (for the thermoelectric effect) or a time variation of the temperature (for the pyroelectric effect)), are required for the energy conversion. ,, These requirements normally lead to relatively complex designs of thermal energy harvesting devices or additional components for systems, which are not desirable for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The flexoelectric effect produces pyroelectricity in parelectric phase which is termed as pyro-paraelectric effect. 12,16 Flexoelectric polarization in solid dielectrics can be written as 11,[13][14][15]17…”
mentioning
confidence: 99%